Measuring business cycles - Burns, Arthur F.; Mitchell, Wesley C. (New York : National Bureau of Economic Research, 1946)
This volume is devoted to a detailed presentation of methods and plans of measuring business cycles. It defines their limitations and presents the justification for their use; it describes patterns of behaviour, and interprets the effects of various treatments upon the basic data used.
"Sources of data": p. 540-550.
lje 18/10/18
Loans
Keywords: Business cycles; Economic methods